The Effect of GPM on Rice Price Volatility in Indonesia: Evidence from Provincial Data with Agricultural Controls - Nur Afini; Tri Haryanto (CV. Global Cendekia Inti, 2026)
Rice price volatility remains a critical challenge for food security and economic stability in Indonesia. This study examines the effect of the Gerakan Pangan Murah (GPM) on rice price volatility using provincial-level panel data with monthly observations from 2023 to 2024. To obtain consistent and unbiased estimates, this study employs a dynamic panel data approach using the Generalized Method of Moments (GMM), specifically the System GMM estimator, which addresses potential endogeneity and captures the persistence of price movements. The model incorporates key agricultural control variables, including rice production, rainfall, and the farmer terms of trade (NTP), representing supply conditions and farmer welfare. The results indicate that rice price volatility exhibits strong persistence over time. After controlling for endogeneity, GPM does not have a statistically significant effect on price volatility, suggesting that the program is more responsive to market conditions rather than functioning as an effective stabilization instrument. In contrast, rice production and rainfall significantly increase price volatility, while NTP tends to reduce it, although with weaker statistical significance. These findings imply that structural factors play a more dominant role than short-term policy interventions in shaping rice price dynamics in Indonesia.